Framework for Evaluating Programming Languages for Computer Graphics - Akram, Mohammed Zeki (2003)
With the continuous increase of the available programming languages over the last few decades, it becomes essential to properly select the language to be used for any field of computation so as to get the best outcome of the language for that specific field. As the fields of Computer Graphics and Computational Geometry are important ones, it becomes essential therefore to make a comparative study of the programming languages which suit those fields best.